The analysis of the results of the Olympic free-style wrestling champions - Latyshev, M.; Latyshev, S.; Korobeynikov, G.; Kvasnytsya, O.; Shandrygos, V.; Dutchak, Y. (Journal of Human Sport & Exercise, 2020)
The successful and effective management of sports training is impossible without the justified forecasting. The retrospective analysis of the sport career of elite sportsmen allows to identify interconnections of the competitions - results on various stages of the sporting career. Analysis of papers showed, there are no researches which would analyse the highest-level sportsmen in wrestling - Olympic champions. Aim of the research - to analyse results of the Olympic champions in wrestling from 1996 to the present day and to discover the main trends and regularities. The analysis included 41 sport careers of winners in freestyle wrestling of the six Olympic Games from 1996 to 2016. The results of wrestlers on international competitions into the four age stages are analysed: the pre-junior age, junior age, senior until the victory at the Olympic Games and a time period after the victory. The majority of the sportsmen (90.3 %) win only once and participate in the OG only once or twice (90.2 %). The retrospective analysis has shown that 48.8 % of wrestlers-champions have performed at the international stage at the cadets age, and 85.4 % of sportsmen at the junior age, over 90 % of them have taken the winning places. Prior to the victory at the Olympic Games 87.8 % of the sportsmen take part at the continental championships, all of them have won medals. And 82.9 % have participated at the world championships, and 91.2 % of them have taken places from 1 to 3.